Efficacy and appropriateness of novel antibiotics in response to antimicrobial-resistant gram-negative bacteria in patients with sepsis in the ICU. Issue 4 (3rd April 2022) - Garduno, Alexis; Martín-Loeches, Ignacio
ABSTRACT: Introduction: There is an ever-increasing range of antibiotic-resistant pathogens that have led to higher community-acquired infections, and substantial mortality rates in critically ill patients. Areas covered: We have critically appraised available evidence through a structured literature review, investigating effective empiric antibiotic administration and appropriateness on outcomes of critically ill patients with an increased risk of developing resistant pathogens. The use of new antibiotics should be determined based on relevant knowledge of their spectrum and properties to provide effective mode of action for critically ill patients. Expert Opinion: Restricting severely ill patients access to new broad-spectrum empirical drugs is not the answer. Rather there should be a focus on identifying host response to infection to differentiate between colonization or contamination and true infection, and the sensitivity to antibiotics used in the intensive care unit (ICU). Management relies on adequate antibiotic administration, the ability to monitor response, and facilitate the cessation of antibiotic treatment. The major determinant of patient success in a patient with a severe infection is the 'right' antibiotic or complementary course of treatment. As an overarching criterion, the following three appropriate "Ds" should be considered: Dosing, Duration, and De-escalation to empirically assess the right antibiotic optimal antimicrobial selection.